2017
DOI: 10.20944/preprints201701.0126.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Iron Deficiency Anemia (IDA) in Pregnant Women of Different Ages in Swat District, Khyber Pakhtunkhwa Pakistan

Abstract: Abstract:The aim of this study was to find out the incidence of anemia in pregnant women of Swat District; to analyze the iron variations and its dietary effects.Data were collected during the periods of January -September 2016. The study of samples comprised of 250 pregnant women in the different trimester. Blood sample from each woman was collected and full blood count (FBC) was conducted through Mindray BC-3000 plus hem analyzer for all pregnant individuals.Confirmed anemic cases were then examined for IDA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Besides poverty, a study conducted in the Khyber Pakhtunkhwa (KPK) province of Pakistan established the relation that the incidence of anemia decreases with a higher level of education, according to the study the rate of anemia was 88% in the pregnant women who had received no formal education [15] . Another research conducted in Thatta revealed that the majority of the women were not aware of what anemia was, and would consider it a blood deficiency.…”
Section: Lack Of Educationmentioning
confidence: 99%
“…Besides poverty, a study conducted in the Khyber Pakhtunkhwa (KPK) province of Pakistan established the relation that the incidence of anemia decreases with a higher level of education, according to the study the rate of anemia was 88% in the pregnant women who had received no formal education [15] . Another research conducted in Thatta revealed that the majority of the women were not aware of what anemia was, and would consider it a blood deficiency.…”
Section: Lack Of Educationmentioning
confidence: 99%